2018
DOI: 10.1093/mnrasl/sly196
|View full text |Cite
|
Sign up to set email alerts
|

Inner bars also buckle. The MUSE TIMER view of the double-barred galaxy NGC 1291

Abstract: Double bars are thought to be important features for secular evolution in the central regions of galaxies. However, observational evidence about their origin and evolution is still scarce. We report on the discovery of the first Box-Peanut (B/P) structure in an inner bar detected in the face-on galaxy NGC 1291. We use the integral field data obtained from the MUSE spectrograph within the TIMER project. The B/P structure is detected as bi-symmetric minima of the h 4 moment of the line-of-sight velocity distribu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
39
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 54 publications
6
39
0
Order By: Relevance
“…In NGC 1291, the stellar populations in the nuclear disc are dominated by an inner bar and we explore these stellar population profiles in a dedicated study in the future. Nonetheless, previous studies of the TIMER team suggest that the centre of NGC 1291 is dominated by a kinematically hot spheroid (de Lorenzo-Cáceres et al 2019a;Méndez-Abreu et al 2019). This idea is consistent with the stellar population and velocity dispersion profiles presented here: the oldest ages, highest metallicities, and highest velocity dispersion are detected in the centre of the galaxy.…”
Section: The Absence Of Kinematically Hot Spheroidssupporting
confidence: 91%
See 2 more Smart Citations
“…In NGC 1291, the stellar populations in the nuclear disc are dominated by an inner bar and we explore these stellar population profiles in a dedicated study in the future. Nonetheless, previous studies of the TIMER team suggest that the centre of NGC 1291 is dominated by a kinematically hot spheroid (de Lorenzo-Cáceres et al 2019a;Méndez-Abreu et al 2019). This idea is consistent with the stellar population and velocity dispersion profiles presented here: the oldest ages, highest metallicities, and highest velocity dispersion are detected in the centre of the galaxy.…”
Section: The Absence Of Kinematically Hot Spheroidssupporting
confidence: 91%
“…These inner bars do not only resemble the shape of regular bars, but they also seem to form and evolve in the same way main bars do (de Lorenzo-Cáceres et al 2019a. In fact, inner bars buckle vertically just like main bars (Méndez-Abreu et al 2019) and even exhibit the same v − h 3 correlation typically associated with bars (Bittner et al 2019).…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…These nuclear discs often host inner bars, nuclear spiral arms and nuclear rings. The formation of inner bars and nuclear spiral arms appear to be simply scaled-down versions of the formation of a bar and spiral arms in the main galaxy disc (Méndez-Abreu et al 2019;de Lorenzo-Cáceres et al 2019), confirming the theoretical work by Wozniak (2015) and Du et al (2015), who also found that nuclear discs and inner bars can be long-lived. Crucially, however, excluding the nuclear disc, the central regions of disc galaxies are dynamically hotter than the regions where the main disc dominates, and thus these processes still need to be better understood.…”
Section: Introductionsupporting
confidence: 82%
“…4). We also detected for the first time the presence of a box/peanut in an inner bar, (in NGC 1291;Méndez-Abreu et al 2019), which demonstrates that the dynamics of inner and main bars is similar (see also de Lorenzo-Cáceres et al 2019).…”
Section: Box/peanutssupporting
confidence: 66%